Pendampingan Pemasaran Jajanan Tradisional di Desa Ngablak Magelang - Adit Setyo Pambudi; Yeny Fitriani; Ahmad Nur Alfianto (Warta Pengabdian Andalas, 2023)
Marketing in rural areas predominantly relies on marketing strategies from the surrounding area, as with traditional snack MSMEs in Ngablak Village. The diversity of products with authentic flavours does not increase sales of traditional snacks in Ngablak Village because a good marketing strategy has yet to support them. This activity aims to improve the marketing strategy of traditional snacks MSMEs using a Participatory Action Research (PAR) approach. The PAR stages include Inquiry by conducting field observations and identifying problems MSMEs face. Action, namely assisting in creating marketing media such as Facebook, Google Maps and branding (logo), reflects on using marketing media to expand MSME marketing. An evaluation was carried out on the impact of this assistance. Marketing strategy assistance involved seven MSMEs of traditional snacks in Ngablak Village and was carried out for 45 days during March-April 2022. The assistance results showed that the PAR approach effectively found the right strategy and solution to increase the marketing of traditional snacks among MSMEs in Ngablak Village. Assistance has made MSME owners aware of the importance of social media, Google Maps and logos in improving the marketing of their traditional snack products.